Instilling Social Attitudes Through Social Studies Learning in Madrasah Ibtidaiyah Students - Muhammad Irham Zainuri (Council: Education Journal of Social Studies, 2024)
This research aims to; 1) Describe the teacher's cultivation of students' social attitudes; 2) Examining the supporters and obstacles to cultivating social attitudes, 3) Identifying the results of cultivating social attitudes through social studies learning. This research method uses qualitative techniques with a field study approach. Then research data was obtained through teachers, principals and students who were interviewed, observed and all other supporting documents were reviewed. The results of data acquisition are analyzed by collecting, interpreting and drawing conclusions. The research results show that; 1) teachers instill social attitudes in students through motivation, exemplary attitudes and taking lessons from the values ​​contained in social studies material to shape students' social character, so that they are skilled in communicating, carrying themselves and having a considerate attitude; 2) supporting the cultivation of students' social attitudes, namely social studies material that is directly related to examples of social facts and phenomena that occur in society and the obstacle is the lack of communication between teachers and parents to follow up on the cultivation of social attitudes at home; 3) the results of instilling social values ​​can be seen from the attitudes shown by students conveying greetings, smiles, greetings, and polite and polite communication etiquette.